Analysis of Health-related Quality of Life Determinants in Adult Ashmatic Patients in a District Hospital in East Jakarta - Hesty Utami Ramadaniati; Sesilia Andriani Keban; Christine Meidiawati (Acta Pharmaceutica Indonesia, 2018)
Background: Uncontrolled asthma leads to patients' poor outcomes and decreases health-related quality of life/HRQoL. Little research has been done to analyze the determinants of  HRQoL in asthmatics patients. Objective: To determine asthma control and  patients' compliance levels, and evaluate the appropriateness of medicine use and determinants of HRQoL. Methods: During this prospective study, adult asthmatic patients who currently experienced asthma attack were evaluated in asthma clinic of a district hospital in Jakarta and administered study questionnaires. Demographic variables and data related to asthma control, patients' compliance level and the appropriate use of medications were summarized using descriptive statistics. The determinants of HRQoL were determined using bivariate and multivariate regression analysis. All data were analyzed using SPSS version 22.0. Results: There were 11 males and 43 females aged approximately 45 years old. More than 50% of the patients had uncontrolled asthma and low level compliance to their medications. Nearly all medicines used were inappropriate according to National Asthma Treatment Guideline. Bivariate correlation test revealed four factors which significantly determined the total score of HRQoL, namely asthma duration (P=0.033), asthma control level (p=0.007), asthma severity level (p=0.001) and the presence of smoke exposure in neighbourhood (p=0.032). Further, multivariate analysis showed only the presence of smoke exposure  significantly affecting patients' quality of life. Conclusion: This study uncovered the majority of patients had uncontrolled asthma status and low level of compliance to their medications. In addition, this study highlighted the exposure of smoke exposure as the solely determinant of HRQoL amongst  asthmatic patients.